Quem é negro, quem é branco: desempenho escolar e classificação racial de alunos - Marília Carvalho (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
This article is based on research undertaken with classes from the 1st to 4th grades of primary education in a public school in the municipality of São Paulo and discusses the differences between the racial classification of school children carried out by teachers and that made by the children themselves. The concept of race adopted is that of social race, that is, a social construct based on an erroneous biological idea but which has proved efficient for maintaining privileges. Concludes that the fact that the difference in school performance between white and black children in the school is greater when the teachers classification is employed in place of self-classification results as much from teachers whitening children with good performance as from their evaluating children, chiefly boys, they perceive as Negroes with greater rigour. It further emphasises that it is not a case of accusing the teachers of deliberate racial discrimination but of investigating the ways in which racism, present in Brazilian society as a whole, also penetrates school relations.